Complicated Diverticular Disease - Coakley, Kathleen M.; Davis, Bradley R.; Kasten, Kevin R. (Clinics in Colon and Rectal Surgery, 2020)
The modern management of colonic diverticular disease involves grouping patients into uncomplicated or complicated diverticulitis, after which the correct treatment paradigm is instituted. Recent controversies suggest overlap in management strategies between these two groups. While most reports still support surgical intervention for the treatment of complicated diverticular disease, more data are forthcoming suggesting complicated diverticulitis does not merit surgical resection in all scenarios. Given the significant risk for complication in surgery for diverticulitis, careful attention should be paid to patient and procedure selection. Here, we define complicated diverticulitis, discuss options for surgical intervention, and explain strategies for avoiding operative pitfalls that result in early and late postoperative complications.
Keywords: diverticulitis; complicated; fistula; colovesical fistula; abscess